2009
DOI: 10.1016/j.worlddev.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Do Workers’ Remittances Reduce the Probability of Current Account Reversals?

Abstract: The paper combines the literature on financial crises in emerging markets and developing economies with that on international migrations by investigating whether the increasingly large flows of workers' remittances can help reduce the probability of current account reversals. The rationale for this stands in the great stability and low cyclicality of remittances as compared to other private capital flows: these properties, combined with the fact that remittances are cheap inflows of foreign currencies, might r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(62 citation statements)
references
References 34 publications
4
57
1
Order By: Relevance
“…Hassan and Holmes (2015) showed that compensation of employees and current personal transfers result in less persistent shocks affecting the current account and quicker ensuing adjustment. Furthermore, Bugamelli and Paternò (2009) demonstrated that compensation of employees and current personal transfers decrease the likelihood of current account crises and thus the likelihood of financial crises. By contrast, certain studies point out that the funds received may push property prices up in the recipient country, which may lead to the misallocation of funds and pose a risk for financial stability (Stepanyan -Poghosyan -Bibolov 2010).…”
Section: Studies Orsolya Csortos -Balázs Kócziánmentioning
confidence: 99%
“…Hassan and Holmes (2015) showed that compensation of employees and current personal transfers result in less persistent shocks affecting the current account and quicker ensuing adjustment. Furthermore, Bugamelli and Paternò (2009) demonstrated that compensation of employees and current personal transfers decrease the likelihood of current account crises and thus the likelihood of financial crises. By contrast, certain studies point out that the funds received may push property prices up in the recipient country, which may lead to the misallocation of funds and pose a risk for financial stability (Stepanyan -Poghosyan -Bibolov 2010).…”
Section: Studies Orsolya Csortos -Balázs Kócziánmentioning
confidence: 99%
“…The current literature seems to primarily characterize remittances as a stabilizing force with many arguing that remittances serve as a reliable source of foreign exchange for remittance receiving economies, in particular when their economies are in a slump. As such, countries with large emigrant populations are believed to be less susceptible to currency crises (Bugamelli & Paterno, 2005;Ratha, 2004). However, if remittances are responsive to portfolio variables, we need to question the assertion that remittances can always be counted on as a reliable source of foreign exchange to counteract speculative outflows and idiosyncratic negative shocks.…”
Section: Introductionmentioning
confidence: 99%
“…or portfolio-diversification motive-see Lueth and Ruiz-Arranz (2007) and papers cited therein. 4 Regardless of the underlying motivation to remit, remittances could be a blessing, if they move counter to home country business cycles, as they will then serve as macroeconomic stabilizers against cyclical contractions or sudden stops (see Bugamelli and Paterno`, 2005). If they are procyclical, on the other hand, they could be a setback, as the drops in remittance receipts observed during cyclical contractions or sudden stops would magnify the damage resulting from such contractions or stops.…”
mentioning
confidence: 99%
“…Our results also confirm that cyclical characteristics of remittances may be different across countries (see Figures 1 and 2, and Table 1, which are generated using data in constant local currency units, that is, real terms). 5 In a cross-country study, Bugamelli and Paterno`(2005) find that remittances, as cheap inflows of foreign currencies, might reduce the probability that foreign investors suddenly flee out of emerging and developing economies, triggering a dramatic current account adjustment.…”
mentioning
confidence: 99%
See 1 more Smart Citation